Peningkatan Hasil Belajar Matematika MelaluiStrategi Project Based Learning DenganMengoptimalkan Alat Peraga(Ptk Pembelajaran Matematika Siswa Kelas VIII F Semester Genap SMP Negeri 2 Gatak Sukoharjo Tahun Ajaran 2014/2015) - Triwati, Cidhadiyah, Drs. Sumardi,M.Si (2015)
This research aims to improve students' mathematics learning outcomes in material geometry of eighth grade students of SMP Negeri 2 Gatak through Project Based Learning strategies by optimizing the porps. This research includes classroom action research. VIII F Class has 31 students consisting of 17 boys and 14 girls as subjects to receive acts and the researcher as the subject to give action. Data collection methods used during the research was the observation, interviews, field notes, test, and documentation. To ensure the validity of the data used triangulation techniques. Data analysis techniques used by researcher are data reduction, data presentation, and take conclusions. The results showed if there is increase in students' mathematics learning outcomes on VIII F of SMP Negeri 2 Gatak. The increase of student learning outcomes can be seen from 1) enthusiastic about the task from the beginning of conditions (40.635%) increased to (86.67%), 2) students who are active gives the opinion from beginning of conditions (15.625%) into (56.67%) , 3) the courage to ask the students from beginning of conditions (18.75%) increased to (53.33%), 4) courage students to answer questions from beginning of conditions (9.375%) increased to (56.67%) and, 5) the increase of test score KKM ≤ 75 from the beginning of conditions (77.41%) increased to (16.66%). It can be concluded that the implementation of Project Based Learning strategies by optimizing the porps on the subject of an upright prism and pyramid can improve student learning outcomes